2019
DOI: 10.3324/haematol.2018.206417
|View full text |Cite
|
Sign up to set email alerts
|

The side population enriches for leukemia-propagating cell activity and Wnt pathway expression in zebrafish acute lymphoblastic leukemia

Abstract: Cancer stem cells have been strongly linked to resistance and relapse in many malignancies. However, purifying them from within the bulk tumor has been challenging, so their precise genetic and functional characteristics are not well defined. The side population assay exploits the ability of some cells to efflux Hoechst dye via ATP-binding cassette transporters. Stem cells have increased expression of these transporters and this assay has been shown to enrich for stem cells in various tissues and cancers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Regulation of p-gp by RPS15A could further affect the number and proportion of stemlike cancer cell side-population (SP) cells (Fig.6) through the e ux mechanism for chemoresistance. [33] In CDDP-treated ESCC cells, the expression level of CD44 signi cantly decreased and apoptosis increased concurrently upon RPS15A deletion (Fig.3). Our ndings are similar to a previous report that showed that CD44 inhibition reduced the adhesion of multiple myeloma cells and reversed the resistance to lenalidomide.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Regulation of p-gp by RPS15A could further affect the number and proportion of stemlike cancer cell side-population (SP) cells (Fig.6) through the e ux mechanism for chemoresistance. [33] In CDDP-treated ESCC cells, the expression level of CD44 signi cantly decreased and apoptosis increased concurrently upon RPS15A deletion (Fig.3). Our ndings are similar to a previous report that showed that CD44 inhibition reduced the adhesion of multiple myeloma cells and reversed the resistance to lenalidomide.…”
Section: Discussionmentioning
confidence: 89%
“…6) through the e ux mechanism for chemoresistance. [33] In CDDP-treated ESCC cells, the expression level of CD44 signi cantly decreased and apoptosis increased concurrently upon RPS15A deletion (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
“…T‐ALL can be induced by the injection of a plasmid containing mouse Myc under control of the zebrafish Rag2 promoter into zebrafish embryos 125 . Although LSC markers have not been established in ALL, Baeten and colleagues 126 isolated T‐ALL LSCs in this model. The authors used the side‐population assay and confirmed the stemness potential of the isolated cells in limiting‐dilution assays.…”
Section: T‐cell Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…myeloid leukemia (AML) and T-ALL [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For T-ALL in particular, zebrafish models have been highly informative, advancing our understanding of T-ALL genetics, pro-and anti-oncogenic interactions between different genes and pathways, tumor heterogeneity, leukemia stem cells, and in screens for new therapeutics [28,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. However, despite the fact that zebrafish T-ALL models had proven to be fertile grounds for study, B-ALL modeling in D. rerio had not been fruitful, with only one low penetrance and long latency line reported [54].…”
Section: Research Perspectivementioning
confidence: 99%